THE RELIGIOUS REVIVAL AS A REASON OF SOCIO-POLITICAL TENSION IN THE NORTH CAUCASUS - Andrey Ivanovich Lukienko (Вестник Северо-Кавказского федерального университета)
The culture-ideological factors that affect the growth of tension in the North Caucasus region are discussed in the paper. Particular attention is paid to the phenomenon of religious renaissance which has played a key role in socio-cultural development of the North Caucasus in the post-Soviet period.